Sustainable bioenergy production - Wang, Lijun, 1971 March 20- (Boca Raton : Taylor & Francis, 2014)
'The energy, water, land and natural resources have been under great pressure to support increasing world population. The availability of fossil energy has been declining worldwide. It is essential to change the global fossil-dependent economy into a sustainable biobased economy. Environmental concern associated with fossil-based energy is another key driver for the emerging bioenergy industry. The bioenergy production from all renewable biological resources such as energy crops, crop residues, forest residues, animal wastes and food processing wastes influence all human activities and environmental sustainability'--
Includes bibliographical references and index.
Keywords: Biomass energy